Updated multi-method estimates of Lake Titicaca's radiocarbon reservoir offset - Eduardo Queiroz Alves; Stéphane Guédron; Christophe Delaere; Mathieu Boudin; Alexandre Chevalier; Tess van den Brande; Gaia Ligovich; Rosa Souza; Peter Eeckhout; Kita Macario (Quaternary Science Reviews, 2025)

Corrigendum to “Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE)” [Quat. Sci. Reviews 338 (2024) 108826] - Stéphane Guédron; Clément Roy; Géraldine Sarret; Julie Tolu; Marie-Pierre Ledru; Sylvain Campillo; Sarah Bureau; Anne-Lise Develle; Charline Guiguet-Covex; Eduardo Queiroz Alves; Mathieu Boudin; Richard Joffre; et al. (Quaternary Science Reviews, 2025)

Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE) - Stéphane Guédron; Clément Roy; Géraldine Sarret; Julie Tolu; Marie-Pierre Ledru; Sylvain Campillo; Sarah Bureau; Anne-Lise Develle; Charline Guiguet-Covex; Eduardo Queiroz Alves; Mathieu Boudin; Richard Joffre; et al. (Quaternary Science Reviews, 2024)

Pottery use across the Neolithic transition in northern Belgium: evidence from isotopic, molecular and microscopic analysis - Dimitri Teetaert; Marieke Vannoorenberghe; Thomas Van de Velde; Mathieu Boudin; Samuel Bodé; Lucy Kubiak-Martens; Mathijs Baert; Frederic Lynen; Philippe Crombé; Pascal Boeckx (Archaeological and Anthropological Sciences, 2024)
This study represents the first extensive residue analysis of prehistoric pottery from northern Belgium. It examines pottery use and culinary practices across the Mesolithic-Neolithic transition, from the late 6th to the early 4th millennium cal BC. Residue analyses were performed on more than 200 samples from nine archaeological sites, representing different cultural groups from this transitional phase. This includes the analysis of charred food residues encrusted on the vessel surfaces by elemental analysis-isotope ratio mass spectrometry (EA-IRMS), gas chromatography-mass spectrometry (GC-MS), stereomicroscopic analysis and Scanning Electron Microscopy (SEM), as well as the analysis of absorbed lipids by gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS). This study provides the first evidence of ruminant dairy fats in Early Neolithic Limburg pottery, supporting the hypothesis that this pottery was produced and used by LBK farmers rather than hunter-gatherer populations. The first indigenous pottery of the Swifterbant culture was frequently used to process freshwater fish (often together with plant foods) and ruminant meat, although several of the studied vessels likely contained mixtures of resources which could also include porcine products. Ruminant dairy is nearly absent from this pottery. Similar results were obtained for pottery of the subsequent Michelsberg culture/Group of Spiere of the late 5th and early 4th millennium cal BC. The limited presence of ruminant dairy fats in this pottery contrasts with the findings for Middle Neolithic pottery from neighbouring regions, providing further evidence for the existence of regional variations in pottery use or culinary practices throughout prehistoric NW Europe. However, our current view of pottery use during the Mesolithic-Neolithic transition in northern Belgium might be biased by the difficulties in distinguishing between wild and domesticated ruminant adipose fats as well as in detecting plant foods through lipid residue analysis.

Vegetation changes in the Grote Nete valley (Campine region, Belgium) during the Boreal: a response to the 9.3 ka event? - Frederike Verbruggen; Wim Z. Hoek; Jeroen Verhegge; Ignace Bourgeois; Mathieu Boudin; Lucy M. Kubiak-Martens; Caroline Ryssaert; Philippe Crombé (Vegetation History and Archaeobotany, 2023)

New insights into cave hyena ethology and the implications for territorial competition with hominins in Late Pleistocene north‐west Europe: the case of Caverne Marie‐Jeanne (Belgium) - Elodie‐Laure Jimenez; MIETJE GERMONPRÉ; MATHIEU BOUDIN (Journal of Quaternary Science, 2022)
Megacarnivore behaviours shape ecological dynamics between their prey and competitors and therefore play a key role in structuring ecosystems. In Late Pleistocene Eurasia, hominins and hyenas were sympatric predators. Since the first discoveries of Crocuta c. spelaea in the 19th century, this ‘bone‐crushing’ species has been identified at most Palaeolithic sites and has inspired many taphonomic studies. Nonetheless, there is still very little known about its reproductive, social and spatial behaviours. We believe that exploring the complexity of the cave hyena's ethology is a way to better understand spatial relationships and niche sharing/partitioning between hominins and other top predators in Pleistocene ecosystems. This paper focuses on the study of Caverne Marie‐Jeanne Layer 4 (Hastière, Belgium), one of the best‐preserved palaeontological sites in the region. The exceptional number of hyena neonates in this assemblage (minimum number of individuals >300) has led us to describe, for the first time, a Late Pleistocene hyena birth den that was reused over a long period of time around 47.6–43k a bp. By bridging the gap between archaeology and palaeontology, we explore the potential of carnivore socio‐spatial organisation and denning habits as an ecological proxy and discuss how these new unique data could help us further understand hominins’ spatial strategy in southern Belgium.

Holes in the spinous processes of woolly mammoth vertebrae: spatial and temporal distribution, and the causes of pathology formation - Sergey V. Leshchinskiy; Yaroslav V. Kuzmin; Mathieu Boudin; Leeli Amon (Journal of Quaternary Science, 2021)
The latest data on holes in the spinous processes of the vertebrae of woolly mammoths, a rare pathology, are presented. This was identified at 19 sites of northern Eurasia. Such destructive changes are recorded ca. 34–12k 14 C a bp , and only two sites dated to >50k and >41k 14 C a bp. The main hypotheses about hole formation are: vertebral abnormalities; bone infections; genetic traits; and unfavourable geochemical environment. The pathology occurred in mammoths of all age groups, and could have arisen at the embryonic stage. There are two types: classic holes associated with osteolytic changes; and very rarely tumour‐like lesions. The most likely cause of the lesions is alimentary osteodystrophy caused by chronic mineral starvation. The aetiology of this disease is usually associated with a deficiency or excess of macro‐ and microelements in the geochemical landscape, and through forage and water this leads to a severe metabolic disorder. Analysis of palaeopathological data shows two waves of geochemical stress in animals, ca. 26–18k and ca. 16–12k 14 C a bp. Therefore, the woolly mammoth extinction can be viewed as a non‐linear function, with two peaks of high mortality corresponding to the Last Glacial Maximum and the Lateglacial.

Divergence, diet, and disease: the identification of group identity, landscape use, health, and mobility in the fifth- to sixth-century AD burial community of Echt, the Netherlands - Barbara Veselka; Giacomo Capuzzo; Rica Annaert; Nadine Mattielli; Mathieu Boudin; Sarah Dalle; Marta Hlad; Charlotte Sabaux; Kevin Salesse; Amanda Sengeløv; Elisavet Stamataki; Dries Tys; et al. (Archaeological and Anthropological Sciences, 2021)

Dying in the Hallstatt Plateau: the case of wooden coffins from Iron Age necropolises in Mallorca (Balearic Islands, Western Mediterranean) and the difficulties in defining their chronology - Manuel Calvo Trias; Mark Van Strydonck; Llorenç Picornell-Gelabert; Mathieu Boudin; Daniel Albero Santacreu; Margalida Coll Sabater; Jaume Garcia Rosselló (Archaeological and Anthropological Sciences, 2020)

The Younger Dryas and Preboreal landscape in the Moervaart area (northwestern Belgium) and the apparent decrease in human occupation - Johanna A. A. Bos; Vanessa Gelorini; Thijs van der Meeren; Jolien Peleman; Mona Court-Picon; Hendrik Demiddele; Philippe De Smedt; Mathieu Boudin; Jacques Verniers; Pascal Boeckx; Philippe Crombé (Vegetation History and Archaeobotany, 2018)